2021
DOI: 10.3390/cells10081885
|View full text |Cite
|
Sign up to set email alerts
|

Ciliary Dyneins and Dynein Related Ciliopathies

Abstract: Although ubiquitously present, the relevance of cilia for vertebrate development and health has long been underrated. However, the aberration or dysfunction of ciliary structures or components results in a large heterogeneous group of disorders in mammals, termed ciliopathies. The majority of human ciliopathy cases are caused by malfunction of the ciliary dynein motor activity, powering retrograde intraflagellar transport (enabled by the cytoplasmic dynein-2 complex) or axonemal movement (axonemal dynein compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 185 publications
(271 reference statements)
0
15
0
Order By: Relevance
“…Dynein assembly factor is important for the assembly of both outer and inner dynein arms. Mutations in central pair and radial spoke genes does not cause laterality defect, adapted from ( Antony et al, 2021 ). Proteins encoded by genes identified in this study are indicated in red.…”
Section: Resultsmentioning
confidence: 99%
“…Dynein assembly factor is important for the assembly of both outer and inner dynein arms. Mutations in central pair and radial spoke genes does not cause laterality defect, adapted from ( Antony et al, 2021 ). Proteins encoded by genes identified in this study are indicated in red.…”
Section: Resultsmentioning
confidence: 99%
“…The authors observed that the AVSD phenotype only occurred in Dnah11 avc4 mutant embryos suffering from heterotaxy. This phenotype is usually attributed to dysfunctions of the embryonic node, and the authors attribute the AVSD as a downstream consequence of perturbations in laterality determination, a general principle that has been concluded by other researchers [ 69 , 83 , 84 ]. In contrast, in the same screen, the authors identified a mutation in the primary cilium IFT gene Ift172 and also a nonsense mutation in the Mks1 (Meckel syndrome, type 1) gene [ 83 ].…”
Section: Primary Cilia and Their Function In The Development Of Speci...mentioning
confidence: 85%
“…By contrast, nodal cilia ultrastructure is characterized by the presence of inner and outer axonemal dynein arms that are located in between microtubules doublet pairs. These dynein arms serve to connect one microtubule doublet to the adjacent/preceding microtubule doublet in a manner that results in the bending motion observed in nodal and motile cilia [ 69 ]. This unique ultrastructure allows nodal cilia to move in an active swirling motion to mediate left–right patterning during late gastrulation and prior to the onset of organogenesis [ 48 ].…”
Section: Primary Cilia and Their Function In The Development Of Speci...mentioning
confidence: 99%
“…B ) Schematic of Dynein-2 motor structure. The two intermediate chains WDR34 and WDR60 bind to the heavy chains as a heterodimeric complex with light chain binding mediated by the N-terminals, adapted from (Antony et al, 2021). C) WDR60 protein structure.…”
Section: Introductionmentioning
confidence: 99%